Antithrombotic use following transient ischaemic attack or ischaemic stroke among older Australians with atrial fibrillation. Issue 11 (November 2014) - Sluggett, J. K.; Caughey, G. E.; Ward, M. B.; Gilbert, A. L.
Abstract: Hospital audits may underestimate anticoagulant use among acute ischaemic stroke patients with atrial fibrillation (AF), as treatment may commence after discharge. To account for this, antithrombotic use in the 4 months after hospitalisation for transient ischaemic attack or ischaemic stroke among AF patients was assessed using claims data. Results suggest that treatment may be commenced soon after discharge and should be considered when assessing prevalence of use.